Role of TrkA signalling and mast cells in the initiation of osteoarthritis pain in the monoiodoacetate model. Issue 1 (January 2018) - Sousa-Valente, J.; Calvo, L.; Vacca, V.; Simeoli, R.; Arévalo, J.C.; Malcangio, M.
Summary: Objective: Aiming to delineate novel neuro-immune mechanisms for NGF/TrkA signalling in osteoarthritis (OA) pain, we evaluated inflammatory changes in the knee joints following injection of monoiodoacetate (MIA) in mice carrying a TrkA receptor mutation (P782S; TrkA KI mice). Method: In behavioural studies we monitored mechanical hypersensitivity following intra-articular MIA and oral prostaglandin D2 (PGD2 ) synthase inhibitor treatments. In immunohistochemical studies we quantified joint mast cell numbers, calcitonin gene-related peptide expression in synovia and dorsal root ganglia, spinal cord neuron activation and microgliosis. We quantified joint leukocyte infiltration by flow cytometry analysis, and PGD2 generation and cyclooxygenase-2 (COX-2) expression in mast cell lines by ELISA and Western blot. Results: In TrkA KI mice we observed rapid development of mechanical hypersensitivity and amplification of dorsal horn neurons and microglia activation 7 days after MIA. In TrkA KI knee joints we detected significant leukocyte infiltration and mast cells located in the vicinity of synovial nociceptive fibres. We demonstrated that mast cells exposure to NGF results in up-regulation of COX-2 and increase of PGD2 production. Finally, we observed that a PGD2 synthase inhibitor prevented MIA-mechanical hypersensitivity in TrkA KI, at doses which were ineffective in wild type (WT) mice. Conclusion: Using the TrkA KI mouse model, we delineated a novel neuro-immune pathway and suggest that NGF-induced production of PGD2 in joint mast cells is critical for referred mechanical hypersensitivity in OA, probably through the activation of PGD2 receptor 1 in nociceptors: TrkA blockade in mast cells constitutes a potential target for OA pain.